2009
DOI: 10.1086/596780
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide System for Improving Influenza Vaccination Rates in Hospital Employees

Abstract: OBJECTIVE To describe and report the progress of a provider-initiated approach to increase influenza immunization rates for healthcare workers. DESIGN Observational study. SETTING The State of Iowa. SUBJECTS Acute care hospitals in Iowa. METHODS Hospitals reported rates of employee influenza vaccination to a provider-based collaborative during 2 influenza seasons (2006–2007 and 2007–2008). Hospital characteristics related to higher vaccination rates were examined. RESULTS One hundred (87.0%) of 115 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…43,44 A strategy involving shared disclosure of vaccination rates has been successful in Iowa, in which a voluntary collaborative involving all 115 acute care hospitals in the state reported institution-specific vaccination rates and strategies used to improve those rates to all member facilities. 45 Although these data were not reported to the general public, this program led to median vaccination rates of 82% in the second year of the program. Coupling such reporting with vaccination mandates would serve to drive these rates even higher.…”
Section: Use Of Vaccination Rates As a Measure Of A Facility's Safetymentioning
confidence: 95%
“…43,44 A strategy involving shared disclosure of vaccination rates has been successful in Iowa, in which a voluntary collaborative involving all 115 acute care hospitals in the state reported institution-specific vaccination rates and strategies used to improve those rates to all member facilities. 45 Although these data were not reported to the general public, this program led to median vaccination rates of 82% in the second year of the program. Coupling such reporting with vaccination mandates would serve to drive these rates even higher.…”
Section: Use Of Vaccination Rates As a Measure Of A Facility's Safetymentioning
confidence: 95%
“…Despite initial concerns that the convenience of an EHR would lead to a high rate of declinations, we observed a voluntary vaccination rate of 77%, which far exceeded national and state averages for healthcare worker vaccination during the 2009 H1N1 influenza pandemic. 6,7 Although causality cannot be proven, the high voluntary vaccination rate may be related to the design and order of the electronic declination form, which prompted users through a series of questions regarding their reasons for declination, educated them on the importance of healthcare worker vaccination, and allowed them to change their minds before submitting the declination form.…”
Section: Discussionmentioning
confidence: 99%
“…The H1N1 pandemic of 2009 highlighted the need for improved efficiency in immunizing large numbers of healthcare workers and providing documentation that each employee had received or declined vaccination. 5,6 Although research suggests that the use of declination forms improves vaccination rates among healthcare workers, the usefulness of declination forms in an electronic format has been little explored. 7,8 Additionally, little is known about the impact of EHRs on vaccination errors or data quality.…”
mentioning
confidence: 99%
“…In a survey of 22 hospitals, Polgreen [19] found that implementation of declination policies increased coverage by a mean of 11.6%. Other studies have shown an association between a hospital's use of declination forms and higher influenza vaccine coverage, but a causal relationship could not be demonstrated with the cross-sectional design [20].…”
mentioning
confidence: 83%